(untitled) (Scientific journal of the Fergana State University, 2025)
This study provides the first confirmed record of Euproctis chrysorrhoea Linnaeus, 1758 (Brown-tail Moth) in Uzbekistan’s Fergana Valley, thereby extending its known distribution into Central Asia. Field surveys at multiple sites in Quvasay (Kokilon – 40°18’21"N, 71°54’50"E; Sufon – 40°22’37"N, 71°57’11"E), Fergana District (Satkak – 40°24’24"N, 71°41’59"E), Kuva District (Akbarobod – 40°32’59"N, 71°55’27"E), and Mingbuloq District ( 40°24’24"N, 71°41’59"E) revealed adult moths on economically important fruit trees (e.g., Prunus cerasus, Prunus domestica, Malus domestica, and Pyrus communis). A total of 71 adult specimens (51 males, 20 females) were collected, from which 7 were selected for detailed morphological analysis. Simple descriptive statistics of key traits (e.g., wingspan, 37.6 ± 1.7 mm) indicate consistency with established descriptions. Observations of the species’ life cycle and host plant damage suggest successful adaptation to the region’s continental climate and orchard ecosystems, emphasizing the need for integrated pest management (IPM). While these findings provide critical baseline data, multi-year studies and broader geographic sampling are essential to evaluate long-term population dynamics and ecological impacts more thoroughly.